Innovative technology strategies for the sustainable development of self-produced energy in the Colombian industry (2023)
This research studies the current state of the Colombian industrial sector, which is focused on self-generation processes. The study’s objective is to search for viable technological strategies that strengthen this particular sector’s competitiveness and sustainable development. The analysis shows that internal combustion engines represent 49% of the technologies used for self-generation. The main fuel used in the sector is natural gas, with a percentage of 56%. The lack of strategies for the use of residual heat and technological inefficiencies caused a loss of 36% in the energy used in the Colombian industrial sector. Thermoelectric generators are a feasible way to recover energy from exhaust gases in engines used for self-generation. Additionally, they allow a 4% reduction in fuel consumption and an improvement in the engine’s energy efficiency. The use of hydrogen as fuel allows a 30% reduction in polluting emissions, such as CO2, CO, HC, and particulate matter. Hydrogen production processes, such as water electrolysis, allow the participation of Colombia’s solar energy potential, leading to sustainable hydrogen production, efficiency (60–80%), and a lower economic cost. In general, the application of thermoelectric generators and the use of hydrogen gas allow the improvement of the Colombian industrial sector’s environmental, social, and economic aspects due to greater competitiveness and the reduction in emissions and operating costs.